2018
DOI: 10.1128/mbio.01738-18
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Is a Key Host Factor forToxoplasmaGRA15-Dependent Disruption of the Gamma Interferon-Induced Antiparasitic Human Response

Abstract: Toxoplasma, an important intracellular parasite of humans and animals, causes life-threatening toxoplasmosis in immunocompromised individuals. Gamma interferon (IFN-γ) is produced in the host to inhibit the proliferation of this parasite and eventually cause its death. Unlike mouse disease models, which involve well-characterized virulence strategies that are used by Toxoplasma to suppress IFN-γ-dependent immunity, the strategies used by Toxoplasma in humans remain unclear. Here, we show that GRA15, a Toxoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 62 publications
4
36
0
1
Order By: Relevance
“…Cytotoxicity to HFF cells induced by nullscript was measured as previously described ( Bando et al, 2018 ). The cell viability was monitored by measuring lactate dehydrogenase (LDH) leakage into the culture medium by using CytoTox96 Non-Radio Cytotoxicity Assay kit (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity to HFF cells induced by nullscript was measured as previously described ( Bando et al, 2018 ). The cell viability was monitored by measuring lactate dehydrogenase (LDH) leakage into the culture medium by using CytoTox96 Non-Radio Cytotoxicity Assay kit (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…With respect to human anti-parasitic effector mechanisms, IFN-γ-induced 2,3 indoleamine dioxygenase (IDO) degrades tryptophan and plays a role for parasite control by astrocytes (119). Interestingly, it has been demonstrated that the parasite aims to restrict anti-parasitic IDO levels in the host cell: the T. gondii effector molecule TgIST inhibits IDO1 mRNA expression and T. gondii GRA15-induced NO antagonizes IFN-γ-dependent IDO levels (120, 121). Importantly, the mechanisms leading to control and elimination of T. gondii in murine and human neurons are unknown.…”
Section: Chronic Infection In the Brain Parenchymamentioning
confidence: 99%
“…In human cells, the effect of iNOS is different. It acts as a pro- Toxoplasma host factor through the GRA15-dependent virulence mechanism in the THP-1/Huh7 coculture mode (Bando et al., 2018). Upregulation of ROS and IDO generated by many cell types leads to inhibition of parasite replication.…”
Section: Resistance To Oxidative Stressmentioning
confidence: 99%